Analisis Laporan Keuangan Untuk Menilai Kinerja Usaha Koperasi Jasa Karyawan Nusa Tiga Unit PISMK - Budi Dharma; Afdillah Nur Aisyah Sinaga; Grace Amalia Tondang (Universitas Labuhanbatu, 2023)
Cooperative financial performance analysis aims to see how the financial position of cooperatives is. Through historical data or financial reports that are used to view and compare individual periods from last year to the current year. The form of research used in this study is research that uses descriptive qualitative methods which describe how a real phenomenon is in accordance with the field which is carried out with actual presentation without any engineering which in this study describes the existence of financial reports used to assess an achievement. employees in the Nusa Tiga Cooperative Unit PISMK. from the results of the research that has been presented, it can be concluded that a conclusion regarding the financial performance of employee service cooperatives during the 2019-2021 financial reporting period can be assessed very well. borrowed voluntarily by members of the cooperative, this system is what causes the cooperative unit to run well and can have a positive impact on society in general and members in particular.